The role of viral marketing in the branding of mobile device products: an exploratory study of a sample of students at the University of Karbala - Abdel Fattah Jassim Zazalan (Iraqi Journal for Administrative Sciences, 2025)
As a result of developments in the business and because of global competition , many business organizations trying to find modern . inventors and thinkers in the field of marketing began thinking to find means to exploit this development by planning new strategies to take advantage to reach the goal , the lowest possible cost , both in the long term or short term .in the this context , large expenditures on promotional campaigns therefore it requires the best use of ICT and its innovative applications ;therefore many international organizations use modern strategy ,such as strategy of viral marketing, which is one of the modern concepts in the field of studies and marketing research based on the concept of the spoken word in the implementation of marketing activities by relying on the internet, by trying to deliver its advertising to the largest number of people, transferring the message content in authenticity ,credibility . Its role in the brand . this concept by studying the most important topics that form the basic conceptual and philosophical framework ,and conduct a survey through the design of a questionnaire distributed to a sample of Internet users of Karbala university students . finally it has been reached to a set of conclusions . The most important it is considered viral marketing a key of success for many organizations ,especially the electronic one ,without this strategy the business organizations cannot work and distribute its products ,ideas ,working in internet market and distinct and superiority in business compared with traditional communication means. a set of recommendation are provided , like application tools for viral marketing concept in environment ,in addition to that making the viral marketing strategy one of the strategic directions for business organizations and consider it one of strategic options for brand advertising .